2002
DOI: 10.1007/s11746-002-0580-9
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain fatty ammonium quaternaries in papermaking

Abstract: A series of long-chain quaternary ammonium halogen esters (UKK-chemicals), quaternary dimethyl tallow epoxypropyl ammonium halogens (EPK1), quaternary ditallow methyl epoxypropyl ammonium halogens (EPK2), and EPK2 oligomers (EPK2P) were synthesized. At acidic, neutral, or slightly basic conditions, EPK1-, EPK2-, EPK2P-, and UKK-chemicals operate as cationic chemicals. They can be used, for example, as stock sizings, surface sizings, or fixatives. Stock sizing, surface sizing, and fixative experiments indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Previous studies on the synthesis and use of new products in the surface sizing, namely, quaternary agents derived from fatty acids, led to positive results concerning the line and dot print quality comparatively to other synthetic agents. However, regarding colour reproduction, the results were not positive [16,21]. It was suggested that the low surface energy of the resultant papers, due to the aliphatic long chain molecules, allows the ink fixation on the paper surface, preventing the spreading and penetration, and thus yielding a good performance in terms of line and dot quality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the synthesis and use of new products in the surface sizing, namely, quaternary agents derived from fatty acids, led to positive results concerning the line and dot print quality comparatively to other synthetic agents. However, regarding colour reproduction, the results were not positive [16,21]. It was suggested that the low surface energy of the resultant papers, due to the aliphatic long chain molecules, allows the ink fixation on the paper surface, preventing the spreading and penetration, and thus yielding a good performance in terms of line and dot quality.…”
Section: Introductionmentioning
confidence: 99%